Cristais de tempo: o cinema de Andrei Tarkovski - Mathias, Roberta Filgueiras (2012)
The idea of this study is to analyze the work of Andrei Tarkovsky, a Russian filmmaker, especially the films Stalker and Mirror as from deleuzian categories, focusing on the perception of time presented in the books Space- Image and Time-Image. We intend to propose a direct relationship between the concept of crystal-image developed in Time-Image and Tarkovsky` s filmography, based on the understanding of the images as crystals reels, which rotate around its own axis, but beyond this rotation have a force that`s the time itself